The Implementation of Wordwall in English learning in a Rural Elementary School with Limited Technological Resources - Syarifatul Ayun; Edi Pujo Basuki, Tiyas Saputri, Nailul Authar (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
The integration of digital technology in education plays a crucial role in fostering interactive and meaningful English language learning, especially for young learners. However, there remains a significant gap between digital learning tools and actual conditions in rural elementary schools, where the main challenges are limited technological facilities and unstable internet access. Although previous research has demonstrated the effectiveness of Wordwall in improving learning outcomes, these studies were mostly conducted in schools with adequate technological support. Therefore, this study aims to explore the implementation of Wordwall in a rural elementary school context and to examine students' perceptions of their use. This study used a descriptive qualitative approach conducted at MI Hidayatul Hikmah Ngoro. Data were collected through classroom observations and questionnaires. The results indicate that Wordwall can be implemented even in technologically limited environments, and that teachers have found unique ways to implement Wordwall in their classrooms, such as using shared devices. Additionally, students expressed positive perceptions, indicating that the use of Wordwall makes learning more engaging and easier to understand. However, several challenges were identified, including limited devices and unstable internet access. In conclusion, Wordwall is a practical and adaptable digital learning tool for educational contexts in rural areas. It is recommended that teachers optimize available resources and implement flexible teaching strategies. Further research is encouraged to test the effectiveness of Wordwall using different research designs or in broader educational settings.